2006
DOI: 10.1519/00124278-200608000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Instability With Resistance Training

Abstract: There are many instances in daily life and sport in which force must be exerted when an individual performing the task is in an unstable condition. Instability can decrease the externally-measured force output of a muscle while maintaining high muscle activation. The high muscle activation of limbs and trunk when unstable can be attributed to the increased stabilization functions. The increased stress associated with instability has been postulated to promote greater neuromuscular adaptations, such as decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 36 publications
2
64
1
11
Order By: Relevance
“…Unlike quiet standing conditions, most of the daily life activities are performed in constantly changing environmental contexts and require instant biomechanical adaptations. Dynamic balance tasks, therefore, have been increasingly recommended recently to monitor functional recovery after injury, since they are believed to reflect the underlying mechanism of postural control strategies utilized in daily life activities (15,16). Hatzitaki et al (17), for example, have shown that balance performance under quiet standing tasks is mostly related to perceiving and processing visual inputs, whereas maintaining balance under dynamically demanding tasks depends highly on rapid processing of somatosensory afferences and initiation of corrective motor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike quiet standing conditions, most of the daily life activities are performed in constantly changing environmental contexts and require instant biomechanical adaptations. Dynamic balance tasks, therefore, have been increasingly recommended recently to monitor functional recovery after injury, since they are believed to reflect the underlying mechanism of postural control strategies utilized in daily life activities (15,16). Hatzitaki et al (17), for example, have shown that balance performance under quiet standing tasks is mostly related to perceiving and processing visual inputs, whereas maintaining balance under dynamically demanding tasks depends highly on rapid processing of somatosensory afferences and initiation of corrective motor responses.…”
Section: Introductionmentioning
confidence: 99%
“…For adolescent boys and girls, however, relatively little information on the extent of sex differences in the muscularity of the trunk is available. Trunk muscles have a critical role in the maintenance of stability and balance when performing movements with the extremities (Andersen et al, 1988), and a strong and stable trunk provides a solid foundation for the torques generated by the limbs (Behm and Anderson, 2006;Kibler et al, 2006). Among the muscle groups located in the trunk, the psoas major is the only muscle that connects the lumber spine and lower limbs (Arbanas et al, 2009) and the largest in cross-section at L4-L5 (McGill et al, 1993;Santaguida and McGill, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These results provide preliminary evidence of the concurrent and criterion-referenced validity of the overall core measures, suggesting that if health-related cut-points were to be developed for the muscular fitness test scores, the low back criterion and overall core measures would produce similar classification of students into a three Fitness Zone classification scheme. From a health-related perspective and assuming LBP is related to low back and core muscular endurance (Balague, Troussier, & Salminen, 1999;Behm & Anderson, 2006), this approach is useful since it can provide insights on the ability of field tests to classify children who are at risk for developing LBP based on testing performance. Incorporating these assessments into physical education will also increase the value of the lesson if physical educators communicate the importance of low back health while concomitantly allowing the students to perform movements that will strengthen the musculature of the low back.…”
Section: Discussionmentioning
confidence: 99%